Given that \( f(x)=(x-6)^{2} \) and \( g(x)=2-3 x \), find (a) \( (f+g)(x)=\square \) (b) \( (f-g)(x)=\square \) (c) \( (f g)(x)=\square \) (d) \( \left(\frac{f}{g}\right)(x)=\square \) Question Help:
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
Let's tackle the given functions step by step! (a) \( (f+g)(x) = f(x) + g(x) = (x-6)^{2} + (2 - 3x) \) To expand \( (x-6)^{2} \): \[ (x-6)^{2} = x^{2} - 12x + 36 \] Now, add \( (2 - 3x) \): \[ (f+g)(x) = x^{2} - 12x + 36 + 2 - 3x = x^{2} - 15x + 38 \] (b) \( (f-g)(x) = f(x) - g(x) = (x-6)^{2} - (2 - 3x) \) Using the expansion from above: \[ (f-g)(x) = (x^{2} - 12x + 36) - (2 - 3x) \] \[ = x^{2} - 12x + 36 - 2 + 3x = x^{2} - 9x + 34 \] (c) \( (f g)(x) = f(x) \cdot g(x) = (x-6)^{2} \cdot (2 - 3x) \) First, we can expand \( (x-6)^{2} \): \[ = (x^{2} - 12x + 36)(2 - 3x) \] To simplify, \[ = 2(x^{2} - 12x + 36) - 3x(x^{2} - 12x + 36) \] \[ = 2x^{2} - 24x + 72 - 3x^{3} + 36x - 108 \] Collecting like terms yields: \[ (f g)(x) = -3x^{3} + 2x^{2} + 12x - 36 \] (d) \( \left(\frac{f}{g}\right)(x) = \frac{f(x)}{g(x)} = \frac{(x-6)^{2}}{2 - 3x} \) This is already in a simplified form, but you can rewrite it as: \[ \left(\frac{f}{g}\right)(x) = \frac{x^{2} - 12x + 36}{2 - 3x} \] Just be cautious with the domain: \( g(x) \neq 0 \Rightarrow 2 - 3x \neq 0 \) which gives \( x \neq \frac{2}{3} \). That's it! You now have \( (f+g)(x) \), \( (f-g)(x) \), \( (f g)(x) \), and \( \left(\frac{f}{g}\right)(x) \) elegantly expressed!